Identification of Antimicrobial Resistance Determinants in Aeromonas veronii Strain MS-17-88 Recovered From Channel Catfish (Ictalurus punctatus) - Tekedar, Hasan C.; Arick, Mark A.; Hsu, Chuan-Yu; Thrash, Adam; Blom, Jochen; Lawrence, Mark L.; Abdelhamed, Hossam (Frontiers in Cellular and Infection Microbiology, 2020)
Aeromonas veronii is a Gram-negative species ubiquitous in different aquatic environments and capable of causing a variety of diseases to a broad host range. Aeromonas species have the capability to carry and acquire antimicrobial resistance (AMR) elements, and currently multidrug resistant (MDR) Aeromonas isolates are commonly found across the world. A. veronii strain MS-17-88 is a MDR strain isolated from catfish in the southeastern United States. The present study was undertaken to uncover the mechanism of resistance in MDR A. veronii strain MS-17-88 through the detection of genomic features. To achieve this, genomic DNA was extracted, sequenced, and assembled. The A. veronii strain MS-17-88 genome comprised 5,178,226-bp with 58.6% G+C, and it encoded several AMR elements, including imiS, ampS, mcr-7.1, mcr-3, catB2, catB7, catB1, floR, vat(F), tet(34), tet(35), tet(E), dfrA3, and tetR. The phylogeny and resistance profile of a large collection of A. veronii strains, including MS-17-88, were evaluated. Phylogenetic analysis showed a close relationship between MS-17-88 and strain Ae5 isolated from fish in China and ARB3 strain isolated from pond water in Japan, indicating a common ancestor of these strains. Analysis of phage elements revealed 58 intact, 63 incomplete, and 15 questionable phage elements among the 53 A. veronii genomes. The average phage element number is 2.56 per genome, and strain MS-17-88 is one of two strains having the maximum number of identified prophage elements (6 elements each). The profile of resistance against various antibiotics across the 53 A. veronii genomes revealed presence of tet(34), mcr-7.1, mcr-3, and dfrA3 in all genomes (100%). By comparison, sul1 and sul2 were detected in 7.5% and 1.8% of A. veronii genomes. Nearly 77% of strains carried tet(E), and 7.5% of strains carried floR. This result suggested a low abundance and prevalence of sulfonamide and florfenicol resistance genes compared with tetracycline resistance among A. veronii strains. Overall, the present study provides insights into the resistance patterns among 53 A. veronii genomes, which can inform therapeutic options for fish affected by A. veronii.